A new ichthyosaur from the Lower Jurassic of Portugal (Iberian Peninsula) - JOÃO PRATAS E SOUSA; ISABEL MORAIS ROLDÃO; MARÍA RÍOS; EDUARDO PUÉRTOLAS-PASCUAL (Acta Palaeontologica Polonica)
Ichthyosaurs were a group of marine Mesozoic reptiles. Their presence in the Portuguese fossil record is scarce and ranges from the Sinemurian to the Toarcian. In this work we describe a new specimen—a nearly complete skull discov ered in the Sinemurian of Praia de Água de Madeiros, São Pedro de Moel, Municipality of Marinha Grande (Portugal). This specimen represents the most complete and best preserved cranial remains from the Iberian Peninsula published to date. Phylogenetic analyses performed identified this specimen as a new genus and species, Gadusarus aqualigneus, the first to be identified in the Iberian Peninsula. The species is phylogenetically recovered as a baracromian ichthyosaur, part of the Neoichthyosauria and Parvipelvia clades.